Increase the feasible step region of biped robots through active vertical flexion and extension motions. Issue 7 (20th May 2016) - Gao, Wei; Jia, Zhenzhong; Fu, Chenglong
SUMMARY: This paper investigates the active vertical motion of biped systems and its significance to the balance of biped robots, which have been commonly neglected by the use of a well-known model called the Linear Inverted Pendulum Model. The feasible step location is theoretically estimated by considering the active vertical movement on a simple point mass model. Based on the estimation, we present two new strategies, namely the flexion strategy and the extension strategy, to enable biped robots to restore balance through active upward and downward motions. The analytical results demonstrate that the robot is able to recover from much larger disturbances using our proposed methods. Simulations of the simple point mass model validate our analysis. Besides, prototype controllers that incorporate our proposed strategies have also been implemented on a simulated humanoid robot. Numerical simulations on both the simple point mass model and the realistic humanoid model prove the effectiveness of proposed strategies.